PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL DISCOVERY LEARNING DI KELAS V SDN 24 PARUPUK TABING KOTA PADANG - Margaret, Amerita; Mansurdin; Zuryanty; Rahmi, Gita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of fifth-grade students at Elementary School 24 Parupuk Tabing, Padang City, in the IPAS (Natural and Social Sciences) subject. Issues included the teacher dominating the instructional process, limited student engagement, and the majority of students failing to meet the established learning objective criteria. To improve IPAS learning outcomes, the Discovery Learning model was implemented using a classroom action research design and a mixed-methods approach combining qualitative and quantitative techniques. The study was conducted over two cycles: two sessions in Cycle I and one session in Cycle II. Each cycle comprised four stages: planning, action implementation, observation, and reflection (serving as the basis for improvement). Data collection involved both test and non-test instruments. The study sample consisted of the class teacher and 29 fifth-grade students from Elementary School 24 Parupuk Tabing, Padang City. Implementing the Discovery Learning model resulted in improved quality of the teaching-learning process and student learning outcomes. By Cycle II, the score for the In-depth Learning Design (RPM) rose from 91.25% to 97.50%. The quality of the teaching-learning implementation—involving both the teacher and student participation—also saw an increase from 85.93% to 96.87%. Furthermore, the average student learning outcome score rose from 76.54 in Cycle I to 89.31 in Cycle II. Based on these results, it is concluded that the Discovery Learning model is highly effective for enhancing the quality of IPAS instruction and improving the learning outcomes of fifth-grade students at Elementary School 24 Parupuk Tabing, Padang City